Philosophical fiction, essays and comprehension in Vilém Flusser's work - Künsch, Dimas A.; de O. Menezes, José Eugenio (Folios, revista de la Facultad de Comunicaciones y Filología, 2018)
This short essay has among its main objectives the dissemination, for a broader latin american public, the life and works of one of the most important contemporary communication minds, the Czech-Brazilian philosopher Vilém Flusser (1920-1991). This text aims to evaluate his work from the epistemological perspective of comprehension, i.e. comprehension as a method, the name for the research project jointly developed by researchers from Faculdade Cásper Líbero, Brazil, and the Facultad de Comunicaciones of the Universidad de Antioquia, Colombia. The authors are above all interested in emphasize the dialogical essence of Flusser's communication thinking and its peculiar fondness regarding the essay as a form for expressing such thinking, which designs, throughout his works, a textual style that was labeled by Abraham Moles as "philosophical fiction".